Analisis Pengukuran Kinerja dengan Metode Balance Scorecard di Sub bagian Humas dan Protokol DPRD Deli Serdang - Harahap, M Gio Vandy; Ginting, Paris Johannes (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
This research aims to analyze the performance of the Public Relations and Protocol Subdivision of the Deli Serdang DPRD using the Balanced Scorecard method. The Balanced Scorecard is a performance measurement tool that evaluates financial and non-financial aspects. The Balanced Scorecard method is considered suitable for public sector organizations because it provides a comprehensive view of organizational performance apart from financial metrics. This research focuses on four perspectives: Financial, Customer, Internal Business Processes, and Learning and Growth. The research findings are expected to provide insight into the effectiveness and efficiency of the Public Relations and Protocol Subdivision, contributing to better decision making and improved performance in the future. The results of the performance of the Deli Serdang DPRD's Public Relations and Protocol when measured using the Balanced Scorecard with four perspectives are one perspective that is not good, namely the financial perspective because there is a budget that does not achieve the set goals, three good perspectives, namely the customer perspective, the internal business process perspective, the growth and learning perspective.